2020
DOI: 10.3389/fpsyg.2019.02956
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in Groups of Different Sizes: The Effects of Punishment and Reputation-Based Partner Choice

Abstract: Reputation and punishment are two distinct mechanisms that facilitate cooperation among strangers. However, empirical research on their effectiveness is mainly limited to relatively small groups and does not address how they enhance cooperation in relatively larger groups. We address this gap in the literature by testing hypotheses from competing perspectives about the extent to which reputation-based partner choice and punishment enhance cooperation in both small and large groups. Prior work recognizes that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…The people-chatting sound is known to invoke feelings of high population density [33], which typically indicates that a large group of people are sharing the same resources. It is known that increasing group size makes cooperation more difficult to achieve and a shared resource less likely to be sustained [26][27][28]57,58]. Therefore, if the motivation for cooperation is focused on a material payoff that is contingent on the resource being sustained (i.e.…”
Section: Having Future Stakes Increases Cooperation But the Reminder Of Presence Of Others Undermines The Positive Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The people-chatting sound is known to invoke feelings of high population density [33], which typically indicates that a large group of people are sharing the same resources. It is known that increasing group size makes cooperation more difficult to achieve and a shared resource less likely to be sustained [26][27][28]57,58]. Therefore, if the motivation for cooperation is focused on a material payoff that is contingent on the resource being sustained (i.e.…”
Section: Having Future Stakes Increases Cooperation But the Reminder Of Presence Of Others Undermines The Positive Impactmentioning
confidence: 99%
“…conspicuous green consumption) [17,[23][24][25]. On the other hand, cooperation in social dilemmas typically decreases with the number of participants, even when a reputation effect is included [26], in part due to greater perceived conflict and lower perceived efficacy [27,28]. A field study also showed that urban residents depleted resources more quickly than rural residents in a dynamic common-pool resource game [29].…”
mentioning
confidence: 99%
“…Here is one possible trajectory. The human species arrives and thrives on the strength of hypertrophied capacities for cooperation and culture, central to which are enhanced mechanisms for reputation tracking (Santos, Rankin, & Wedekind, 2011), social prediction (Frith & Frith, 2006), and normative forms of conformity and enforcement (Kelly & Setman, 2020;Wu, Balliet, Peperkoorn, Romano, & Lange, 2019). These initially outward-oriented social mechanismssome of which may themselves have culturally evolved and been socially acquired (Heyes, 2018) are reoriented Putting the pieces together: Self-control as a complex interaction of psychological processes Fritz Strack, Roland Deutsch and Bleen Abraham Julius-Maximilians-Universität Würzburg, Lehrstuhl für Psychologie II, D-97070 Würzburg, Germany.…”
Section: Conflict Of Interest Nonementioning
confidence: 99%
“…This seems theoretically impossible insofar as punishment is the mechanism for avoiding defection precisely when trust is impossible, such that it is not a valid substitute for trust whether in big or small organizations. A recent empirical study shows that punishment only guarantees trust and reciprocity in one-shot interactions ( Wu et al, 2020 ). A meta-analysis across 18 societies clearly concluded that the effectiveness of punishment in promoting cooperation depends on the level of trust ( Balliet and Van Lange, 2013 ).…”
Section: Game Theory’s Basic Moral-psychological Assumptionsmentioning
confidence: 99%